Penerapan Metode Bahtsul Masail Dalam Pembelajaran Fiqh Untuk Meningkatkan Daya Kritis Santri - Hibatullah Abdul Kudus, Hilyas; Oktafiami, Cahaya (Tarbiyatu wa Ta'lim: Jurnal Pendidikan Agama Islam, 2025)
Bahtsul Masail is a forum for the study of religious issues, bahṡul masail functions as a forum for studying Islamic religious issues, in this forum discusses and decides on issues that require legal certainty in the field of fiqh. The Bahtsul Masail method is a method of discussion or deliberation used to solve various religious problems as carried out in various Islamic Boarding Schools related to Islamic law in fiqh learning in order to increase the critical power of students in developing religious knowledge in the field of Islamic Law (Fiqh science). The purpose of this study is to find out the extent of the critical power of students in Islamic boarding schools in understanding the fiqh learning material through the Bahtsul Masail method. This type of research is a field study through a qualitative approach where in the technique of collecting data through Library Research (Literature Studies) from various sources that are  from various sources put forward by experts in the field. The results of the study show that the stages in the Bahtsul Masail method include the preparation, opening, core and closing stages which include problem analysis, answer search, answer delivery, answer categories, argumentative debate, answer formulation, and tabayyun and endorsement, which is then aikhiri with the closing, the efforts made by a Kiai in the formation of students' critical thinking skills, including giving opportunities and rewards to students who are achievements, given opportunities in self-development, training for students to have proficiency in detecting problems and solving these problems which ends with conclusions/decisions. Through this method, it is hoped that it can provide significant changes to the condition of a student's critical ability so that they are able to analyze, synthesize, solve problems, conclude and evaluate.